Strategic design of electric vehicle charging stations within power distribution networks - Amit Kumar; Priyanka Raturi Semwal (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
For the optimal placement and distribution of EV charging stations, they must be integrated within the power distribution network more effectively. Several parameters are taken into account as part of this process, such as proximity to load centers, capacity of the power system, and traffic volume. The common charging station location distant from the load centers has been established to enhance the quality of power and reduce 5–10 % of distribution losses. Additionally, site location should also include the area land cost and this cost in the urban area is estimated to be about $500 to $2000 per square meter and other zoning regulations. In the design, the service radius of charging stations is also an important factor; Keeping the battery's DOD between 50 % and 70 % yields an estimated driving range of 150–200 km, which suggests a distance between stations of 50–70 km. In this case, the discount rate of 5 % can be adopted for O&M costs over the planning horizon of 20 years while the capital costs of provision of each station varies from $ 50,000 to $ 200,000 depending on the size of the station. The establishment of a large network for charging the EVs will enhance the power balance of the system thus reducing power losses whilst increasing the penetration of electric vehicles by integrating these numerical aspects together with technology and environmental considerations.